2017
DOI: 10.1038/s41598-017-05667-5
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed autophagic response underlies augmentation of renal ischemia/reperfusion injury by type 2 diabetes

Abstract: Diabetes mellitus is a major risk factor for acute kidney injury (AKI). Here, we hypothesized that suppression of autophagic response underlies aggravation of renal ischemia/reperfusion (I/R) injury by type 2 diabetes mellitus (T2DM). In OLETF, a rat model of T2DM, and its non-diabetic control, LETO, AKI was induced by unilateral nephrectomy and 30-min occlusion and 24-h reperfusion of the renal artery in the contralateral kidney. Levels of serum creatinine and blood urea nitrogen and tubular injury score afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 67 publications
3
22
0
Order By: Relevance
“…4C). Although our previous studies showed that impaired activation of an AMP-activated protein kinase (AMPK) and hyperactivation of mTORC1 are involved in suppressed autophagy in OLETF (Murase et al 2015;Muratsubaki et al 2017), we could not detect significant effects of empagliflozin on AMPK or mTORC1 in OLETF in the noninfarcted myocardium (Oshima et al, unpubl. observation).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…4C). Although our previous studies showed that impaired activation of an AMP-activated protein kinase (AMPK) and hyperactivation of mTORC1 are involved in suppressed autophagy in OLETF (Murase et al 2015;Muratsubaki et al 2017), we could not detect significant effects of empagliflozin on AMPK or mTORC1 in OLETF in the noninfarcted myocardium (Oshima et al, unpubl. observation).…”
Section: Discussionmentioning
confidence: 66%
“…; Muratsubaki et al. ), we could not detect significant effects of empagliflozin on AMPK or mTORC1 in OLETF in the noninfarcted myocardium (Oshima et al., unpubl. observation).…”
Section: Discussionmentioning
confidence: 76%
“…As the correlation between blood βOHB and renal NGAL expression was modest ( r = −0.41), mechanisms other than increased βOHB are possibly involved in renoprotection by canagliflozin with pre‐MI fasting. Activation of AMPK is one of the candidates, but the present results showed that the contribution of AMPK to renoprotection against diabetes mellitus‐induced worsening of CRS was limited. It has been suggested that the reduction of oxygen consumption in the proximal tubules and prevention of cellular senescence are the mechanisms of renoprotection by an SGLT2 inhibitor, but whether these mechanisms are involved in amelioration of CRS should be examined in future studies.…”
Section: Discussionmentioning
confidence: 65%
“…First, OLETF spontaneously develop diabetes mellitus primarily by hyperphagia as a result of a lack of cholecystokinin-A receptor in the brain, and they show the typical phenotype of type 2 diabetes mellitus (i.e., obesity, hyperinsulinemia and hypertriglyceridemia) 19,20 . Second, OLETF at the ages of 25-30 weeks show an early stage of diabetic nephropathy: lower serum creatinine level with protein urea than that in Long-Evans Tokushima Otsuka rats (LETO), non-diabetes mellitus control rats 8,21,22 . Third, we previously found that renal susceptibility to type 1 CRS was higher in OLETF than in LETO 8 .…”
Section: Introductionmentioning
confidence: 98%
“…In these cells, viruses inhibit lysosomal degradation in the maturation step of autophagy and use autophagic membranes for the formation and release of the viral particles. 98 In type 2 diabetes, low micromolar CQ could inhibit autophagy and cause apoptosis of podocytes and exacerbate nephropathy. 93 In fact, basal autophagy has been proposed to play a pivotal role in sustaining mitochondrial function in lymphoma, and low CQ concentration may cause apoptosis in susceptible lymphoma cells.…”
Section: Cq Regulates Tissue Responses To Metabolic and Inflammatory mentioning
confidence: 99%